Workspace awareness for groupware - Gutwin, Carl; Greenberg, Saul (1996)
Shared physical workspaces allow people to maintain up to the minute knowledge about others’ interaction with the workspace. This knowledge is workspace awareness, part of the glue that allows groups to collaborate effectively. In this paper, we present the concept of workspace awareness as a key for groupware systems that wish to support the fluid interaction evident in face-to-face collaboration. We discuss why workspace awareness is difficult to support in groupware systems, and then present a conceptual framework that groupware designers can use as a starting point for thinking about and supporting awareness. KEYWORDS: Workspace awareness, groupware, CSCW
Formato de archivo: PDF. -- Disponible también en línea (Cons. 21-04-2008)
Conference on Human Factors in Computing Systems (CHI’96), p. 208-209. Vancouver, 1996.
Keywords: GROUPWARE; APLICACIONES COLABORATIVAS